EFFECT OF ANNEALING CYCLES ON DEEP DRAWABILITY OF LOW CARBON TITANIUM ADDED STEEL - Iskandar Muda; Azwar Manaf (Jurnal Sains Materi Indonesia, 2020)
EFFECT OF ANNEALING CYCLES ON DEEP DRAWABILITY OF LOW CARBON TITANIUM ADDED STEEL. Maximum mechanical properties and deep drawability of low carbon titanium added steels was obtained after heat treatment with simulation batch annealing cycles in an industrial process. The effect of holding times and holding temperatures on deep drawability were studied using tensile test for measuring normal anisotropy (r-value) and strain hardening exponent (n-value). Scanning electron microscope were employed for observation of microstructure in steel sheets. X-ray diffraction with pole figure techniques were also used for measuring texture of annealing. Results showed that as the temperature was increased up to 900 oC, both r and n values increased gradually and peaked in the temperature of 850 oC. This results showed that formability of sheet materials increased until batch annealing temperature reach 850 oC as increasing the ratio of intensities {111} /{100}. The largest mean r value of almost 2.6 was obtained in slow heating at holding temperature of 850 oC with n value of 0.27.